Chelation assisted exfoliation of layered borides towards synthesizing boron based nanosheets. Issue 4 (12th January 2017) - James, Asha Liza; Jasuja, Kabeer
Abstract : Selective extraction of inter-layer metal atoms by the chelating agent delaminates layered metal borides into boron based nanosheets. Abstract : The ability to exfoliate tightly bound layered ionic solids has vastly expanded the realm of 2D materials beyond graphene. A crucial step in such exfoliation strategies involves extraction of the inter-planar atoms holding the layers together. Here we present a chelation assisted selective extraction strategy for exfoliating layered metal borides, a family of layered ionic solids that are isostructural to intercalated graphite, with metal atoms sandwiched between graphenic planes of boron. We present evidence for the exfoliation of two metal borides, namely magnesium diboride and aluminium diboride, into aqueous dispersions of few-layer-thick boron based nanosheets, by employing chelation assisted targeted extraction of the inter gallery metal atoms. Chemical analysis of the nanosheets reveals a substantial loss of metal atoms and the presence of boron-planes decorated with hydride, hydroxyl, and oxy-functional groups that are likely derived from the aqueous milieu. The nanosheets exhibit a distinct crumpled morphology with micron-scale lateral dimensions and few layer thickness. These functionalized nanosheets derived from metal borides present promising platforms to leverage the potential of nanoscaled boron. The soft chemical exfoliation approach demonstrated here achieves delamination in a single step under ambient conditions without any additional aides like sonication and holds immense prospects for exfoliating a host of 3D precursors.